Crisis of Water Resources on the Ulan Buh Desert Oases, Inner Mongolia, China-A Case Study of Dengkou County - Zhong-ju MENG; Yong GAO; Yi YU; Xiao-meng REN (Journal of Integrative Agriculture, 2013)
Hetao Plain, composed of hundreds of oases, is one of the most important grain-producing areas in China. Most crops, especially wheat and corn, depend on irrigation, thus water availability is a key issue for grain productivity on this land. The Yellow River is the main water source for irrigation and a crisis of water resources for agricultural use occurs because of increasingly reduced river flows and water-using competition with industry and human residential use. In order to understand the current situation and distribution of water resources on these oases, we collected 20-yr's data of river runoff, irrigation volumes, infiltration and precipitation to examine the relationships between water resources distribution and its agricultural use. We found that the oasis in Dengkou county was short of water resources with a water deficit rate of 5.14% in 2010. Based on the trend of the data, water deficit will continue to increase as the population grows in the future. Water resource is a limiting factor to agricultural development in this region and proper management of water use and strategies for water resource conservation are urgently needed. Especially, based on our results we suggest that current irrigation methods need to be greatly improved to save the water that was lost from evaporation.